Mi amiga tiene dislexia = My friend has dyslexia - Tourville, Amanda Doering, 1980-; Sorra, Kristin (Mankato, Minn. : Picture Window Books, 2012)
"Explains some of the challenges and rewards of having a friend with dyslexia using everyday kid-friendly examples--in both English and Spanish"--Provided by publisher.
Includes index.
Keywords: Dyslexia -- Juvenile literature